Disadvantageous Oil Tariffs and Dynamic Consistency - Maskin, Eric; Newbery, David (American Economic Review, 1990)
A large importer who places relatively greater weight on future than current oil consumption will import less oil in the future than if it were able to commit itself in advance to future tariffs, and may find itself worse off than if it were unable to impose tariffs at all. Futures markets and storage modify these adverse effects and may avoid the problem of dynamic inconsistency. Copyright 1990 by American Economic Association.